Education Between Future Perspective and Demand for Quality and Accreditation - Mohammad AL-Momani; Elham Mahmoud Rababa (LPPM Universitas Terbuka, 2023)
The study aimed to identify the current education system between looking to the future and the issue of quality and reliability, as the issue of quality and accreditation many educators and specialists in the field from the principle of providing a high level of reliability to all educational and educational programmers and youth in the teacher, the curriculum and the educational environment, whether in school stage university mother represented, in addition to the importance of the presence of modern technology in education and its impact on future generations in the future; where this study came to shed light on the importance of education and its impact on individuals and society through the introduction of all kinds of educational and technological innovations; The study followed the qualitative analytical approach based on the theoretical research study. This study concludes that it is necessary to work on strengthening education, whether in school or university, with all the new knowledge and modern technologies, the impact of which is reflected on students and society, contributing to the continuity of progress, growth, and prosperity of societies.